Isolated Torticollis May Present as an Atypical Presentation of Meningitis. (21st October 2012) - Chirurgi, Roger; Kahlon, Samrina
Abstract : Background . Bacterial meningitis is a life-threatening medical emergency that requires urgent diagnosis and treatment. Diagnosis is infrequently missed if the patient presents with the classic symptoms of fever, headache, rash, nuchal rigidity, or Kernig or Brudzinski sign. However, it may be less obvious in neonates, elderly, or immunocompromised patients. Meningitis which presents as isolated torticollis, without any other signs or symptoms, is exceedingly rare. Objective . To identify an abnormal presentation of meningitis in an adult immunocompromised patient. Case Report . We present a case of an adult diabetic male who presented multiple times to the ED with complaint of isolated torticollis, who ultimately was diagnosed with bacterial meningitis. Conclusion . We propose that in the absence of sufficient explanation for acute painful torticollis in an immunocompromised adult patient, further evaluation, possibly including a lumbar puncture may be warranted.